Nikolaus II. Esterházy und die Kunst - Körner, Stefan (2013)
Prince Nikolaus II Esterházy (1765–1833) is known as one of the greatest collectors and patrons of the arts of his time. Based on an ideological, historical and psychological framework, the biography fully illustrates his lifetime achievement with regard to the visual and performing arts. Against the backdrop of political and social changes in Europe between the French Revolution and the Year Of Revolutions 1848, this book discusses to what extent art served as a medium and strategy in the aristocracy’s effort to preserve its leading role in society, despite a loss of power as the Estates-based society was gradually replaced by one based on social classes. Fürst Nikolaus II. Esterházy (1765–1833) war einer der größten Sammler und Kunstförderer seiner Zeit. Die Biographie stellt seine Lebensleistung in allen Bereichen der bildenden und darstellenden Kunst dar und begründet diese ideengeschichtlich und psychologisch. Vor dem Hintergrund der gesellschaftlichen und politischen Veränderungsprozesse Europas, zwischen Französischer Revolution und Vormärz, wird die Rolle der Kunst als Medium und Strategie der sozialhistorischen Behauptung der Adelswelt analysiert, die im Wandel von der Standes- zur Klassengesellschaft ihre Machtstellung einbüßte.